APLIKASI IRIGASI BERSELANG (INTERMITTENT IRRIGATION) PADA BUDIDAYA TANAMAN PAK CHOI (BRASSICA RAPA L.) DENGAN MEDIA TANAM PADATAN DIGESTAT DAN TANAH - Ahmad Rifki Maulana; Oktafri Oktafri; Ahmad Tusi (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2018)
The aim of this research is to know the effectiveness of intermittent irrigation and water productivity analysis, analysis of optimum irrigation interval on plant material of mixed solids of digestat and soil mixture, analysis of optimum combination of digestat solid and soil for plant, and growth and yield analysis Pak Choi plant production. The research was conducted at Greenhouse Plastic Department of Agricultural Engineering Faculty of Agriculture, University of Lampung in November 2016 until December 2016. This research uses two factors of observation, namely Composition of Planting Media and Interval of Irrigation Time. This research used 4 mixed treatment of plant media composition, that is D0 (Digestat 0%: Soil 100%), D1 (Digestat 20%: Soil 80%), D2 (Digestat 40%: Soil 60%), and D3 (Digestat 60% : Soil 40%). Each mixture of media was done 3 repetitions, so that 12 pots were observed. The results showed that the combination of planting medium D1 (Digestat 20%: 80% soil) resulted in a high enough on pak choi of 122.7 grams, while for treatment result D0, D2 and D3 there was a less significant difference. The provision of irrigation water with intermittent irrigation does not significantly affect the growth and yield of Pak choi plant. Longer water delivery intervals still provide a good effect on the results of pak choi plant production due to the addition of solid digestat on the planting medium. The highest water use productivity was achieved by treatment D1 with an average of 774 g /m3. Keywords : Digestat, Intermittent Irrigation, Media Planting, and Pak Choi.